Spatial–temporal distribution characteristics and influencing factors of immovable cultural heritage in Hubei, China - Wenyuan Zhang; Lihong Ma; Jiayu Xu; Yujie Peng (Scientific Reports)
Abstract Immovable cultural heritages are nonrenewable and irreplaceable excellent cultural resources. With the help of the GIS spatial analysis method, Geodetector and location entropy, this paper explores the spatial and temporal distribution characteristics and influencing factors of 1070 nationally and provincially designated immovable cultural heritage sites in Hubei, China. The physical geographical factors, historical and humanistic factors, and their explanatory power indexes are constructed, which provide a scientific quantitative analysis of influencing factors for the spatial distribution of cultural heritages. The results show that the kernel density distribution of immovable cultural heritages in Hubei Province is agglomeration, and Wuhan is the dominant nuclear. The number of cultural heritages in different historical periods is unevenly distributed. The average center of cultural heritages in each period was located in Jingshan. The spatial differentiation of these cultural heritages is affected by multiple factors. Among natural factors, topographic and geomorphic factors such as elevation and slope have a more significant effect, whereas among social and economic factors, the cultural atmosphere and the number of permanent residents have the most significant explanatory power. These findings may help local governments formulate more effective measures for the protection of immovable cultural heritages.